Contrast-Enhanced Fluid Attenuated Recovery (FLAIR) Sequence of Magnetic Resonance Imaging for Tuberculous Meningitis in Paediatric Population - Fahad Ali, Waseem Mirza, Mohammad Asad, Maria Anum, Saqib Qamar Ishaqi, Rabail Raza, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tuberculous meningitis is a well known consequence of tuberculosis, related with top mortality and morbidity in emergent nations. Prompt recognition can play a noteworthy part in rewarding and treating patients of tuberculous meningitis. Aim: To Ascertain the accuracy of contrast FLAIR MRI for diagnosis of tuberculous meningitis in children considering CSF culture as benchmark. Setting: Radiology Department of AKUH. Study Design: Cross-sectional study. Place and Duration: This study was conducted at Department of Radiology, Aga Khan University Hospital, Karachi From January 2015 to December 2016 Sample Selection: A total of 148 paediatric patients with clinical impression of tuberculous meningitis for 6 months were incorporated in study. FLAIR images were carried out from skull base to vertex in coronal plane from nasion to occipital protuberance with interval of 1.5 mm and 5 mm sections were taken. Data Analysis: Percentage were calculated for presentation of variables including FLAIR imaging findings, CSF Culture results and gender. Sensitivity, specificity, accuracy, positive and negative predictive values of FLAIR calculated and presented in percentages. Chi square test was applied taking P <0.05 as significant. Results: 148 patients of which 67 were males (45.3%) and 81 were females (54.7%). Contrast enhanced FLAIR MRI test correctly identified 78.68 % of healthy individuals and labeled 76.68 % of the diseased correctly. Final stat showed 43 % of the people were correctly identified as true positive, 94 % of the people who were found negative were disease free in reality. The conclusive certainty for the imaging was found to be 78.37%. Conclusion: MRI Contrast FLAIR imaging is a justifiable tool which can assist in before time identification of tuberculous infection of brain and primary start of antituberculous medications without waiting for CSF results which require up to weeks. Keywords: Magnetic resonance imaging, Fluid attenuated inversion recovery, tuberculous meningitis.